Specific Identification of Fraction I-Positive Pasteurella pestis Colonies on Antiserum-Agar Plates - Albizo, Johnnie M. (1968)
A method is described for the use of antiplague serum in Blood Agar Base plating media to detect fraction I-positive Pasteurella pestis. The antiserum was produced conveniently and in large volume in rabbits by use of Cutter plague vaccine combined with Freund's complete adjuvant. P. pestis colonies were specifically identified within 48 hr after plating by the presence of a precipitin ring surrounding each colony. The basis of the test was shown to be a precipitin reaction between fraction I antigen released from P. pestis colonies after chloroform vapor treatment and fraction I antibody present in the antiserum-agar medium.